Global estimates of the need for rehabilitation based on the Global Burden of Disease study 2019: a systematic analysis for the Global Burden of Disease Study 2019. Issue 10267 (19th December 2020) - Cieza, Alarcos; Causey, Kate; Kamenov, Kaloyan; Hanson, Sarah Wulf; Chatterji, Somnath; Vos, Theo
Summary: Background: Rehabilitation has often been seen as a disability-specific service needed by only few of the population. Despite its individual and societal benefits, rehabilitation has not been prioritised in countries and is under-resourced. We present global, regional, and country data for the number of people who would benefit from rehabilitation at least once during the course of their disabling illness or injury. Methods: To estimate the need for rehabilitation, data from the Global Burden of Diseases, Injuries, and Risk Factors Study 2019 were used to calculate the prevalence and years of life lived with disability (YLDs) of 25 diseases, impairments, or bespoke aggregations of sequelae that were selected as amenable to rehabilitation. All analyses were done at the country level and then aggregated to seven regions: World Bank high-income countries and the six WHO regions (ie, Africa, the Americas, Southeast Asia, Europe, Eastern Mediterranean, and Western Pacific). Findings: Globally, in 2019, 2·41 billion (95% uncertainty interval 2·34–2·50) individuals had conditions that would benefit from rehabilitation, contributing to 310 million [235–392] YLDs. This number had increased by 63% from 1990 to 2019. Regionally, the Western Pacific had the highest need of rehabilitation services (610 million people [588–636] and 83 million YLDs [62–106]). The disease area that contributed most to prevalence was musculoskeletal disorders (1·71 billion people [1·68–1·80]), with low back pain being the most prevalent condition in 134 of the 204 countries analysed. Interpretation: To our knowledge, this is the first study to produce a global estimate of the need for rehabilitation services and to show that at least one in every three people in the world needs rehabilitation at some point in the course of their illness or injury. This number counters the common view of rehabilitation as a service required by only few people. We argue that rehabilitation needs to be brought close to communities as an integral part of primary health care to reach more people in need. Funding: Bill & Melinda Gates Foundation.